1999
DOI: 10.1515/bc.1999.120
|View full text |Cite
|
Sign up to set email alerts
|

The Two SH2-Domain-Containing Inositol 5-Phosphatases SHIP1 and SHIP2 Are Coexpressed in Human T Lymphocytes

Abstract: The activation of many hematopoietic cells via cytokine receptors, as well as B and T cell receptors, leads to the tyrosine phosphorylation of Shc and its association with both Grb2-Sos1 complexes and with a 145 kDa protein referred to as the SH2 containing inositol 5-phosphatase (SHIP1). In a search of putative 5-phosphatase isoenzymes, we have isolated a second SH2 domain containing inositol 5-phosphatase, referred to as (SHIP2). Both SHIP1 and SHIP2 are coexpressed in human T lymphocytes. This was shown at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
(29 reference statements)
2
24
0
Order By: Relevance
“…Differential expression of the lipid phosphatase SHIP-1 in CEM and Jurkat cells Previous works have shown that the Jurkat leukemic cell line is deficient in SHIP-1 at the protein level, but that CEM cells express the protein normally (Bruyns et al, 1999;Freeburn et al, 2002;Horn et al, 2004). To confirm that difference in our cell lines, we carried out Western blotting analysis with specific antibodies raised against SHIP-1 and another inositol lipid phosphatase, namely SHIP-2.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Differential expression of the lipid phosphatase SHIP-1 in CEM and Jurkat cells Previous works have shown that the Jurkat leukemic cell line is deficient in SHIP-1 at the protein level, but that CEM cells express the protein normally (Bruyns et al, 1999;Freeburn et al, 2002;Horn et al, 2004). To confirm that difference in our cell lines, we carried out Western blotting analysis with specific antibodies raised against SHIP-1 and another inositol lipid phosphatase, namely SHIP-2.…”
Section: Resultsmentioning
confidence: 76%
“…Antiphosphotyrosine antibody (4G10) was from UBI (Lake Placid, NY, USA). Monoclonal anti-IkBa antibody (MAD10B) and polyclonal anti-SHIP-2 antibody were a gift from R Hay (St Andrews, Scotland) or previously described (Bruyns et al, 1999;Muraille et al, 1999). H 2 O 2 , ALLN and aminotriazole were from Sigma (St Louis, MO, USA).…”
Section: Cell Culture Antibodies and Reagentsmentioning
confidence: 99%
“…The absence of SHIP proteins has been reported in the human T-cell line Jurkat which has been derived from a patient with T-cell acute lymphoblastic leukemia. 33,25 Indeed, immunoblot analysis confirmed the absence of detectable SHIP proteins in Jurkat cells ( Figure 1a, lane 1). This result was obtained with anti-SHIP antibodies directed against the first NPXY motif of SHIP (S-5) and was confirmed with anti-SHIP antibodies directed against a Cterminal region of SHIP (P1C1) and an N-terminal region of SHIP (V19) (data not shown).…”
Section: Constitutive Activation Of Akt In Jurkat Cells Is Downregulamentioning
confidence: 65%
“…17,18 However, the human T-cell leukemia cell line Jurkat does not express detectable amounts of SHIP proteins. 33 By using an inducible expression system (Tet-On), expression and activity of SHIP was restored in Jurkat cells and the biochemical and biological effects were analyzed. In this study, evidence is provided that restoration of SHIP activity in Jurkat cells causes a reduced proliferation of these cells without detectable cell death by apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the molecular mechanism involved, we used the Jurkat T leukemic cell line. Jurkat cells do not expressed SHIP-1 at the protein level 21,25,26 because of a bi-allelic null mutation and a frameshift deletion 27 and we restored SHIP-1 expression in these cells using lentiviral transduction method. As a negative control, Jurkat cells were transduced with an empty vector (hereafter referred as Jurkat Ev).…”
Section: Ship-1 Protects Primary T Lymphocytes and T Leukemic Cells Fmentioning
confidence: 99%